(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The researches conducted in the area of the Hellenistic temple by the University of Rome “La Sapienza”, in collaboration with the University of Bologna as well as with the Politecnico of Bari (archaeological campaigns 2003-2008), have made possible a deeper investigation of the functional, historical and urban aspects of the urban pattern of Gortyna. In the mentioned sector, close to one of the most important sacred areas in this town (the sactuary of Apollon Pythios), public buildings play a central role and they are object of progressive architectural modifcations in connection with their functional evolution. The sondages have revealed a very articulated stratigraphical succession; the best attested phases are the earliest ones (end of the II-beginning of the I century B.C.) and overall the period between the IV and the VIII century A.D. The analysis of the ceramic adds new quantitive data to the results of former investigations carried out in the area of the Praetorium and in the “Colini sondages”, confirming a large presence of some productions (LRC, African red slip ware); moeover the study offers new research axes about the centres of production of some different pottery (amphoras, late red slip ware) and about the commercial contacts of the island overall between Late Ancient times and the age of Heraclios.